Ace2 safeguards embryonic hematopoietic stem and progenitor cell production by restraining Nlrp3-mediated pyroptosis - Jun Xia; Lingxue Shen; Yining Liu; Lu Wang; Feng Liu (Proceedings of the National Academy of Sciences, 2025)
During vertebrate embryogenesis, hematopoietic stem and progenitor cells (HSPCs) originate from hemogenic endothelium (HE) in the dorsal aorta through endothelial-to-hematopoietic transition (EHT). While basal inflammation is essential for this process, excessive immune activation disrupts HSPC emergence. Here, we identify angiotensin-converting enzyme 2 (Ace2), a key component of renin–angiotensin system, as a crucial anti-inflammatory regulator of embryonic hematopoiesis in zebrafish and mice. Loss of Ace2 impairs HE specification and reduces nascent HSPC production. Mechanistically, transcriptomic profiling reveals that ace2 deficiency leads to aberrant activation of NLR family pyrin domain containing 3 (Nlrp3) signaling and pyroptosis in vascular endothelial cells. Importantly, pharmacological inhibition of Nlrp3 or Caspase-1 restores HSPC emergence upon ace2 deficiency, consistent with treatment with exogenous angiotensin-(1–7) [Ang-(1–7)], a downstream product of Ace2 enzymatic activity. Moreover, Ace2 knockdown in mouse embryos phenocopies the defects in zebrafish, demonstrating evolutionary conservation of ACE2 in developmental hematopoiesis in mammals. Together, our findings uncover an essential role for ACE2 in maintaining a permissive inflammatory environment for HSPC development and suggest therapeutic potential for targeting the ACE2/Ang-(1–7)/Nlrp3-pyroptosis axis in inflammatory hematopoietic disorders.